Network Analysis Highlights the Complementary Roles of Active and Passive Restoration for Birds in a Restored Landscape Mosaic - Antonelli, Victor R. [UNESP]; Ballarin, Caio S. [UNESP]; Cavarzere, Vagner [UNESP]; Fonseca, Renata C. B. [UNESP] (Wiley, 2025)
ABSTRACT Birds are essential in connecting conserved and restored habitats in anthropogenic landscapes, acting as ‘mobile links’ that enhance habitat connectivity. They contribute to key ecological functions that support habitat recovery. Despite their sensitivity to habitat changes, bird assemblages in restored landscapes show varied responses due to factors like the restoration technique employed. This study uses the species–habitat network approach to assess how different restoration techniques and bird functional traits influence bird habitat use and connectivity in the Atlantic Forest. We adapted network metrics—among‐module connectivity and within‐module degree ( c ‐ and z ‐scores, respectively)—to quantify how habitat types contribute to landscape connectivity and to assess how bird functional traits explain patterns of occupancy across restored fragments. We show that actively restored habitats tend to have more exclusive bird species compared to conserved forests, whereas naturally regenerated forests support a broader range of shared bird species. While active restoration often promotes species with specific habitat needs, it may have a more limited role in landscape connectivity, compared to natural regeneration, which better integrates habitat types. These findings suggest that combining active and passive restoration strategies can maximise landscape connectivity, with active restoration providing habitat for species with particular requirements and passive restoration enhancing broader ecosystem recovery through bird occupation. Additionally, our findings indicate that bird functional traits have low explanatory power for patterns of bird habitat use in restored landscapes, emphasising the value of a more detailed network approach that includes species‐specific interactions. Still, the species–habitat network approach revealed key species that help connect different habitat types, highlighting the role of bird species in landscape cohesion. Future research should explore finer network resolutions and larger spatial scales to better capture species movement and habitat dynamics within restoration gradients. RESUMO As aves são elementos essenciais na conexão entre habitats conservados e restaurados em paisagens antrópicas, atuando como ‘elos móveis’ que potencializam a conectividade da paisagem. Elas contribuem para funções ecológicas‐chave que sustentam a recuperação do habitat. Apesar de sua sensibilidade a mudanças no habitat, as assembleias de aves em paisagens restauradas apresentam respostas variadas, influenciadas por fatores como a técnica de restauração empregada. Este estudo utiliza a abordagem de redes espécie‐habitat para avaliar como diferentes técnicas de restauração e os traços funcionais das aves influenciam o uso do habitat e a conectividade na Mata Atlântica. Foram adaptadas métricas de rede—conectividade entre módulos e grau dentro do módulo (valores c e z, respectivamente)—para quantificar como os tipos de habitat contribuem para a conectividade da paisagem e para avaliar como os traços funcionais das aves explicam os padrões de ocupação entre fragmentos restaurados. Demonstramos que habitats restaurados ativamente tendem a abrigar espécies de aves mais exclusivas em comparação com florestas conservadas, enquanto as florestas em regeneração natural sustentam uma gama mais ampla de espécies compartilhadas. Embora a restauração ativa frequentemente promova espécies com necessidades habitat‐específicas, ela pode ter um papel mais limitado na conectividade da paisagem quando comparada à regeneração natural, que integra melhor os tipos de habitat. Estes resultados sugerem que a combinação de estratégias de restauração ativa e passiva pode maximizar a conectividade da paisagem: a restauração ativa provê habitat para espécies com requisitos particulares, e as restaurações passivas potencializam a recuperação mais ampla do ecossistema por meio da ocupação por aves. Adicionalmente, nossos resultados indicam que os traços funcionais das aves possuem baixo poder explicativo para os padrões de uso do habitat em paisagens restauradas, reforçando o valor de uma abordagem de rede mais detalhada que inclua interações espécie‐específicas. Ainda assim, a abordagem de rede espécie‐habitat revelou espécies‐chave que auxiliam na conexão entre diferentes tipos de habitat, destacando o papel de espécies de aves na coesão da paisagem. Pesquisas futuras deveriam explorar resoluções de rede mais refinadas e escalas espaciais maiores para capturar de forma mais adequada o movimento das espécies e a dinâmica dos habitats dentro dos gradientes de restauração.